Serum HOXA10 and EMX2 expression and estrogen metabolism-related changes in endometriosis and adenomyosis - Guo, Yueli; Zha, Lu; Wang, Yan; Chen, Jue; Lin, Qingping (Journal of Medical Biochemistry, 2026)
Background: This study was designed to characterize serum HOXA10 and EMX2 expression and to examine their association with estrogen-related biochemical alterations in endometriosis (EMT) and adenomyosis (AM).Methods: A total of 168 women of reproductive age treated in our hospital between May 2024 and October 2025 were included, comprising 64 controls, 49 patients with EMT, and 55 patients with AM. Fasting serum samples were collected during the proliferative phase of the menstrual cycle. Serum estradiol (E2) and estrone (E1) were measured by electrochemiluminescence immunoassay and enzyme-linked immunosorbent assay, respectively. Serum RNA was isolated and reverse-transcribed after quality assessment. The expression levels of HOXA10, EMX2, and six estrogen metabolism-related genes were then measured by real-time quantitative PCR. Correlations between the core genes and estrogen-related indicators were analyzed, and ROC analysis was used as an exploratory assessment.Results: Serum HOXA10 expression was decreased, whereas EMX2 expression was increased, in both the EMT and AM groups compared with controls. The HOXA10/EMX2 ratio was also reduced and showed a greater decline in AM (P